PENINGKATAN HASIL BELAJAR IPA MENGGUNAKAN LINGKUNGAN SEKITAR SISWA KELAS IV SDN 01 PONTIANAK SELATAN - Pancarudin, Pancarudin; Rosnita, Rosnita; Kresnadi, Heri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractAbstract: This study aimed to describe the learning outcome 'knowledge of natural sciences using sorrounding environment fourth grade students of SDN 01 Pontianak Selatan.Metode study is a descriptive form of classroom action research, and collaborative. Data collection techniques used are direct observation and measurement techniques and data collection tool using the observation sheet and booklet. Data analysis technique used is using the calculation formula - average. This research was conducted for 4 cycle.es, with the result of 1) the ability of teachers plan learning, which is as follows in the first cycle of 2.36, in the second cycle of 2.68, in third cycle of 3.13 and the fourth cycle of 3.63. 2) The ability of teachers to implement learning, which is as follows in the first cycle of 2.23, in the scond cycle 2.74, in the third 3.20 , and the fourth cycle of 3.55. 3) Results of learning, which is as follows, 52.4. in the first cycle, 80.86 in the second cycle, 87.5 in the third cycle and 90.96 in the fourth cycle. Keywords: Enhancement, Learning outcomes, Natural science, Sorrounding ecosystem